Role of yqiG pseudogene in Escherichia coli towards biohydrogen production - Zakaria, Muhammad Azman (2017)
Biohydrogen gas has a great potential as alternative energy and it is considered as environmental friendly energy source. Extensive studies have been carried out on the production of biohydrogen from Escherichia coli (E. coli). E. coli was used due to its accessibility of full genome and well characterized proteins. Interestingly, there are some of pseudogenes present in E. coli genome. The pseudogenes were considered as non-functional genes as result of genetic variability. In this study, we found that yqiG is one of the pseudogenes in E. coli that is essential for biohydrogen production. The deletion of yqiG has reduced the biohydrogen productivity in comparison to the E. coli wild type as control. The objective of this study is to investigate the role of yqiG pseudogene of E. coli during hydrogen production. The yqiG single gene deletion strain and ASKA strains were used throughout the study. The yqiG mutant strain has significantly interrupted biohydrogen productivity and suppressed glucose consumption up to 50% compared to wild type, respectively. In addition, overexpressed yqiG protein in the wild type via pCA24N-YqiG had increased the hydrogen productivity to 56 μmol H2/mg protein from glucose compared to control which only 38 μmol H2/mg protein. Similar pattern was observed from formate fermentation whereas wild type producing yqiG protein dominated the biohydrogen productivity about 141.8 μmol H2/mg protein. Higher expression of formate hydrogen lyase components (fdhF, hycE and fhlA) were observed in mutant yqiG strain. In contrast, the yqiG mutation causes down regulation of pflB and pykF of glycolysis as well as formic acid accumulation in the fermentation broth compared to the wild type strain. The pflB and pykF encode pyruvate kinase and pyruvate formate lyase, respectively. We conclude that the yqiG protein is important in the conversion of phosphoenolpyruvate to pyruvate and utilization of pyruvate to formate for hydrogen production. Thus, yqiG pseudogene makes an important contribution during hydrogen metabolism in E.coli.